Clinical characteristics associated with bone mineral density improvement after 1-year alendronate/vitamin d3 or calcitriol treatment: Exploratory results from a phase 3, randomized, controlled trial on postmenopausal osteoporotic women in China. Issue 31 (August 2018) - Liao, Er-Yuan; Zhang, Zhen-Lin; Xia, Wei-Bo; Lin, Hua; Cheng, Qun; Wang, Li; Hao, Yong-Qiang; Chen, De-Cai; Tang, Hai; Peng, Yong-De; You, Li; He, Liang; et al.
Abstract : Abstract: Baseline and on-treatment characteristics, including age, obesity, calcium intake, and bone turnover markers, may predict the bone mineral density (BMD) response in women with postmenopausal osteoporosis (PMO) to 1 to 2 years of antiresorptive therapy and/or vitamin D supplementation. This study aimed to explore clinical characteristics associated with 12-month BMD improvement in Chinese women with postmenopausal osteoporosis (PMO). In this post hoc analysis of a previous phase 3 multicenter, randomized controlled trial, Chinese PMO women who were treated with once weekly alendronate 70 mg/vitamin D3 5600 IU (ALN/D5600) or once daily calcitriol 0.25 mcg, and had measurements of 1-year lumbar spine BMD (LS-BMD) and on-treatment bone turnover markers (BTMs) were included in the analysis. In Chinese PMO patients on ALN/D5600, 1-year LS-BMD change was negatively correlated with age ( β  = −0.00084, P  < .01), dietary calcium ( β  = −0.0017, P  = .07), and procollagen type 1 N-terminal propeptide (P1NP) change at month 6 ( β  = −0.000469, P  = .0016), but positively with body mass index (BMI) ( β  = 0.00128, P  = .08); baseline P1NP above the median was associated with a significantly greater BMD percentage change at the lumbar spine ( P  = .02) and the total hip ( P  = .0001). In the calcitriol group, a significant 1-year LS-BMD increase was associated with BMI ( β  = 0.0023, P  = .02), baseline P1NP ( β  = 0.00035, P  = .0067), history of prior vertebral fracture(s) ( β  = 0.034, P  < .0001) and baseline serum 25(OH)D level ( β  = −0.00083, P  = .02). The presented findings from Chinese postmenopausal osteoporotic women suggested clinically meaningful baseline and on-treatment characteristics predicting BMD improvement after 1 year of ALN/D5600 treatment, which differed from calcitriol treatment with baseline identifiable associations. The study remained exploratory and further accumulation of evidence is needed. Abstract : Supplemental Digital Content is available in the text